Proteolytic analysis of Trichoderma reesei in celluase-inducing condition reveals a role for trichodermapepsin (TrAsP) in cellulase production. (1st June 2019) - Daranagama, Nayani Dhanushka; Shioya, Koki; Yuki, Masahiro; Sato, Haruna; Ohtaki, Yuki; Suzuki, Yoshiyuki; Shida, Yosuke; Ogasawara, Wataru
Abstract: Filamentous fungi produce a variety of proteases with significant biotechnological potential and show diverse substrate specificities. Proteolytic analysis of the industrial enzyme producer Trichoderma reesei has been sparse. Therefore, we determined the substrate specificity of T. reesei secretome and its main protease Trichodermapepsin (TrAsP) up to P1 position using FRETS-25Xaa-libraries. The role of TrAsP was analyzed using T. reesei QM9414 and the deletant QM∆ trasp in Avicel. We observed higher activities of CMCase, Avicelase, and Xylanase in QM∆t rasp compared to that of QM9414. Saccharification rate of cellulosic biomass also increased when using secretome of QM∆ trasp but the effect was not significant due to the absence of difference in BGL activity compared to QM9414. Higher TrAsP was produced when monosaccharides were used as a carbon source compared to cellulase inducers such as Avicel and α-sophorose. These results elucidate the relationship between TrAsP and cellulase production in T. reesei and suggest a physiological role for TrAsP.